Equações polinomiais: soluções algébricas, geométricas e com o auxílio de derivadas - Pontes, Ronaldo da Silva (2013)
Since ancient times, for about 4000 years, many people have already solved polynomial equations in their daily lives through problems and practices constructions. In this paper, we study some algebraic and geometric methods used for solving polynomial equations. We start talking about factoring and division of polynomials, device Briot-Ruffini, relationships Girard, theorem of the complex roots and the theorem of the rational roots research. In chapter 2, we will show the methods algebraic of Viète, Cardano, Ferrari and Euler, and some geometric methods, such as the of proportion, of the Descartes and Thomas Carlyle and of the conicas. In section 3, we see the derivative of a polynomial, Newton's iterative method, translation of coordinate axes, using the derived for to find coeffcients of the reduced form of the polynomial and with the aid of derivatives show a method of resolution the equations 3rd and 4th degrees.